Impact of telitacicept on gonadal function in adult female patients with systemic lupus erythematosus: a prospective cohort study - Zhang, Ziyan; Zeng, Qianni; Wen, Yabin; Zhou, Yuqing; Zhang, Lihua (Frontiers in Immunology, 2025)
Background/AimTelitacicept has shown promise in disease control of systemic lupus erythematosus (SLE). This study aimed to evaluate the impact of telitacicept on gonadal function in adult female patients with SLE.MethodsIn this prospective cohort study, adult female SLE patients aged 18 to 45 years were included and divided into telitacicept and non-telitacicept group. Hormonal levels of estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), and anti-Müllerian hormone (AMH) were measured at baseline, month 1, 3, and 6 post-treatment. Generalized estimating equations adjusting for baseline confounders was used.ResultsA total of 78 patients were included, with 38 in the telitacicept group and 40 in the non-telitacicept group. Telitacicept significantly decreased PRL and LH levels (both adjusted Ptime<0.001), with greater reduction compared to non-telitacicept treatment (adjusted Pgroup=0.001 and <0.001, respectively). In the multivariate logistic regression, telitacicept treatment was associated with a significantly lower incidence of abnormal PRL levels at month 6 (odds ratio=0.138, 95% confidence interval: 0.036-0.527, P = 0.004). The levels of AMH and E2 were increased and the levels of FSH were decreased (all adjusted Ptime<0.05), while the changes of AMH, E2 and FSH levels were similar between the two groups (all adjusted Pgroup>0.05). SLE Disease Activity Index scores were significantly lower with telitacicept compared to non-telitacicept treatment at month 1, 3 and 6 post-treatment (all P<0.05). The incidence of adverse events was similar between the two groups.ConclusionTelitacicept demonstrates significant benefits in improving gonadal function and controlling disease activity in female SLE patients.